Primary Systemic Al Amyloidosis Presenting as Temporal Arteritis - Hakan Emmungil; Melike Kalfa; Burcu Başarık; Hasip Kahraman; Ferhat Tanhan; Banu Yaman; Atiye Öztürk; Zehra Erdemir; Gülşen Kandiloğlu; Vedat İnal; Yasemin Kabasakal (Case Reports in Rheumatology)
Temporal arteritis is most common vasculitis in elderly and imitated by miscellaneous disorders. Temporal artery biopsy is the gold standard test in the diagnosis of giant cell arteritis (GCA). Hereby, we describe a case of a 67-year-old man who presented initially with temporal arteritis; however, a lip biopsy then revealed AL amyloidosis. In this respect, temporal artery biopsy should be performed for definitive diagnosis of GCA particularly patients with systemic symptoms and treatment resistant.